Implementasi Push Notification pada Aplikasi Antrean Pasien Berbasis Android - Mohamad Styvani Hendi S; Tri Widodo, S.T., M.Kom (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This study aims to implement and evaluate the push notification feature in an Android-based patient queue application to improve service efficiency and user satisfaction. The research process includes several stages: needs analysis, system design, feature implementation, functional testing, and user satisfaction testing using the User Satisfaction method. Data were collected through a Likert-scale questionnaire covering five aspects: ease of use, interface design, response speed, information relevance, and overall satisfaction. The results show that the application successfully provides real-time queue information through push notifications, enhancing user convenience. The average user satisfaction rate exceeded 80%, with the highest score of 88% achieved in the information relevance aspect. Reliability testing using Cronbach’s Alpha obtained a coefficient value of 0.87, indicating that the questionnaire instrument was reliable and internally consistent. Therefore, the implementation of push notifications has proven effective in improving user experience and service efficiency in digital patient queue management.